Determination of optimum location for carbon monoxide detectors in car cabins - Ghezavati, Hamidreza (2011)
There is limited study on CO concentrations exposure in car cabin in Malaysia. The specific objectives of this study are: (i) to determine the entry routes of CO in a stationary car (ii) to determine entry for moving car on congested, less congested and not congested roads (iii) for use results from objective (i) and (ii) as input parameters on computational fluid dynamics (CFD) to predict optimum location of detector. The car was driven with different modes of air conditioning: recirculation and fresh air intake at two different times of day (morning and evening) from September through December 2008. The CFD simulations using the realizable k-ε model was used to predict optimum location of detector in car cabin. The simulation result was then verified via experimental data from literature. The k-ε model is the most common turbulent model due to its accuracy for this type of conditions. More than 84 percent of CO entry into car cabin was through the vent in the rear trunk and through the diffuser of the air-conditioning system; i.e. 16 percent cabin leak cracks, holes, gaps or other openings in the car cabin. The highest mean CO exposure was experienced for the recirculation mode, location Middle Ring Road II (MRRII), and time of day pm and am, with mean CO concentrations of 19.7 ppm and 18.5 ppm respectively for average of 70 trips. Experimental measurements on CO level was done in WIRA car cabin, the fan of the car drove the flow through the front diffuser in three levels: high, medium and low flow rates equal to 0.0587 kg/s , 0.0443 kg/s and, 0.0293 kg/s, respectively. The experimental data was used to verify the simulation results. Three-dimensional CFD using FLUENT 6.3 showed that the optimal detector location was found to be in the middle of ceiling where the detector can measure the highest CO in the least amount of time and for easy maintenance.